2022
DOI: 10.3390/jof8111191
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Probiotic and Yeast Products in Enhancing Livestock Feeds Utilization and Performance: An Overview

Abstract: The intensive use of antibiotics as growth-promoting agents in animal production has resulted in the spread of animal antibiotic resistance and possibly human antibiotic resistance. Based on this premise, it is significant to explore an alternative approach to preventing infectious diseases and promoting animal growth and health. Yeast as the main natural growth promoter in livestock nutrition has been extensively studied for decades. Numerous yeasts and yeast-containing products are produced, marketed, and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 53 publications
0
15
0
1
Order By: Relevance
“…Polysaccharides in fruit and vegetable juices are hydrolyzed to produce useful components in the fermentation process, such as oligosaccharides which can be used as bifidus factors for human nutritional and health functions ( Fonteles et al, 2018 ). It has been reported that after yeast fermentation, the nutritional value of fruit and vegetable juices improves and is easier to absorb, mainly during yeast fermentation, amino acids, B vitamins and other active compounds (such as glutathione and ergosterol) can be formed from fruit and vegetable juices, which improves the nutritional value of the product ( Pang et al, 2022 ).…”
Section: The Improvement Effect Of Probiotics On Fruit and Vegetable ...mentioning
confidence: 99%
“…Polysaccharides in fruit and vegetable juices are hydrolyzed to produce useful components in the fermentation process, such as oligosaccharides which can be used as bifidus factors for human nutritional and health functions ( Fonteles et al, 2018 ). It has been reported that after yeast fermentation, the nutritional value of fruit and vegetable juices improves and is easier to absorb, mainly during yeast fermentation, amino acids, B vitamins and other active compounds (such as glutathione and ergosterol) can be formed from fruit and vegetable juices, which improves the nutritional value of the product ( Pang et al, 2022 ).…”
Section: The Improvement Effect Of Probiotics On Fruit and Vegetable ...mentioning
confidence: 99%
“…Yeasts are unicellular, ubiquitous eukaryotic organisms traditionally isolated from soil, water, plants, honey, and food stocks (Pang et al, 2022 ). Numerous yeast and yeast‐derived products are produced and marketed as food supplements, functional foods, and pharmaceuticals, including anticancer and antimicrobial compounds (Roohvand et al, 2017 ).…”
Section: Therapeutic Drugs Of Microbial Originmentioning
confidence: 99%
“…The yeast is therefore frequently studied as an additive to livestock feed. 137 The underlying mechanisms could be either that binding to the yeast decreases the pathogens’ binding to intestinal epithelium or that binding decreases the transit time through the gut and therefore facilitates pathogen elimination 138 ( Figure 4 ). The binding is inhibited in the presence of mannose, indicating the association of these bacteria to the surface mannose residues present on S. boulardii .…”
Section: Gut Mycobiomementioning
confidence: 99%